PENGARUH PRIVASI, KEAMANAN DAN KEPERCAYAAN TERHADAP NIAT BERTRANSAKSI ONLINE DI SITUS SHOPEE (Studi Kasus Pada Masyarakat Jl. Hibrida RT. 07 Kota Bengkulu) - Bora Sanjaya; Sri Ekowati (UM. Bengkulu, 2022)
This study aims to determine the effect of privacy, security and trust on the intention to transact online on the Shopee site in Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the consumer on the Shopee site which is located in Bengkulu City. The sampling method used a non-probabilty technique, namely accidental sampling. The number of respondents in this study were 120 people. Methods of data collection using a questionnaire. The data analysis technique uses Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely t-test and f-test.The results of this study can be concluded that the Privacy variable has a positive effect on Consumer Online Transaction Intentions, Security has a positive effect on Consumer Online Transaction Intentions, Trust has a positive effect on Consumer Online Transaction Intentions, and Privacy, Security and Trust together have a positive and significant effect on Consumer Online Transaction Intention.Â Keywords : Privacy, Security, Trust and Online Transaction IntentionÂ